Does Job Accessibility Matter in the Suburbs? Black Suburbia, Job Accessibility, and Employment Outcomes - Hyunjoo Eom (Land, 2022)
The spatial mismatch hypothesis of John Kain proposes that geographic separation between residential locations and jobs creates a spatial barrier in accessing job opportunities, which has a negative impact on labor market outcomes. A key hypothesis is that Black populations have limited accessibility to suburban job opportunities due to residential segregation in the city, resulting in lower employment and earnings. However, the spatial structure of the U.S. metropolitan area has changed since then, with increased polycentric employment growth and Black suburbanization. This challenges Kain’s original hypothesis that residential segregation in the city creates a spatial barrier in accessing jobs. The spatial pattern of mismatch has changed and demonstrates a mismatch between Black suburbs and suburban jobs. Then, what role does job accessibility play in the change in the spatial pattern of mismatch? Does job accessibility continue to matter in the suburbs? Or, are there other more important neighborhood characteristics affecting labor market outcomes? The findings demonstrate that job accessibility remains closely associated with Black labor market outcomes. In Chicago, job accessibility has higher marginal effects on Black employment, especially in predominantly Black neighborhoods. However, in Atlanta, where a majority of the Black population lives in the suburbs, having a higher percentage of Black residents in the neighborhood negates the effects of job accessibility. Instead, the share of Black residents becomes a more significant factor in employment. The findings demonstrate that the effect of job accessibility varies by the spatial pattern of mismatch. Job accessibility becomes less important in highly segregated suburbs, but the share of Black residents matters more in labor market outcomes. In metropolitan areas with the traditional mismatch pattern, job accessibility is significantly associated with employment and earnings, especially in neighborhoods where the majority of the Black population remains segregated in the city.